Mucosal melanoma of the cranio-facial region: Surgical challenges and therapeutic options - Thierauf, Julia; Plinkert, Peter K. (Auris, nasus, larynx, 2019)
OBJECTIVE: Although current therapeutic options for cutaneous melanoma (CM) are constantly improving survival, mucosal melanoma (MM) remains a rare tumor disease with a poor clinical outcome. While radical surgery is the gold standard, clear margin resections in the head and neck area are particularly critical due to high density of vulnerable structures. Adjuvant therapeutic options increases local control and data on the effect of systemic agents is sparse. The aim of this study was to elucidate surgical challenges in the craniofacial area and to evaluate the effect of local and systemic therapy in Head and Neck Mucosal Melanoma (HNMM). - METHODS: In total, 21 patients with nasal mucosal malignant melanoma were included in this study over the course of 20 years in two German tertiary referral centers. Patient characteristics and conducted therapy as well as clinical outcomes were analyzed retrospectively. - RESULTS: By performing survival analysis for multimodal therapies, we observed a superiority effect of interferon therapy compared to surgery with radiation and surgery alone in the first therapeutic approach. However, patients treated with surgery alone in a recurrent setting showed the best outcome. - CONCLUSION: Both, Interferon and radiation as adjuvant therapies, demonstrated survival benefits in initial treatment compared to surgery alone. Analysis after recurrence, however, revealed salvage surgery as a reliable and powerful tool to prolong post-recurrence survival without exposing palliative patients to the risk of severe adverse events from systemic therapies.